Association of dietary patterns, circulating lipid profile, and risk of obesity - Pan, L; Shi, K; Lv, J; Pang, Y; Guo, Y; Pei, P; Du, H; Millwood, I; Yang, L; Chen, Y; Gao, R; Yang, X; et al. (Wiley, 2023)
Objective The aim of this study was to simultaneously explore the associations of major dietary patterns (DP) with lipid profiles and the associations of these profiles with general and central obesity risks and to evaluate the extent to which the metabolites mediate such associations. Methods Habitual food consumption of 4778 participants with an average age of 47.0 from the China Kadoorie Biobank was collected using a 12-item food frequency questionnaire. Plasma samples were analyzed via targeted nuclear magnetic resonance (NMR) spectroscopy to quantify 129 lipid-related metabolites. Anthropometric information was measured by trained staff. Results Two DPs were derived by factor analysis. The newly affluent southern pattern was characterized by high intakes of rice, meat, poultry, and fish, whereas the balanced pattern was characterized by consuming meat, poultry, fish, fresh fruit, fresh vegetables, dairy, eggs, and soybean. The newly affluent southern pattern was positively associated with 45 metabolites, which were positively associated with risks of obesity at the same time. The global lipid profile potentially explained 30.9%, 34.7%, and 53.1% of the effects of this DP on general obesity, waist circumference-defined central obesity, and waist-hip ratio-defined central obesity, respectively. Conclusions The newly affluent southern pattern points to an altered lipid profile, which showed higher general and central obesity risks. These findings partly suggest the biological mechanism for the obesogenic effects of this DP.